Nod-Like Receptors: Key Molecular Switches in the Conundrum of Cancer - Kent, Andrew; Blander, J. Magarian (Frontiers in Immunology, 2014)
It is believed the immune system can contribute to oncogenic transformation especially in settings of chronic inflammation, be activated during immunosurveillance to destroy early neoplastic cells before they undergo malignant outgrowth, and finally, can assist growth of established tumors by preventing clearance, remodeling surrounding tissue, and promoting metastatic events. These seemingly opposing roles of the immune system at the different stages of cancer development must all be mediated by innate signaling mechanisms that regulate the overall state of immune activation. Recently, the cytosolic Nod-like receptor (NLR) pathway of innate immunity has gained a lot of attention in the tumor immunology field due to its known involvement in promoting inflammation and immunity, and conversely, in regulating tissue repair processes. In this review, we present all the current evidence for NLR involvement in the different stages of neoplasia to understand how a single molecular pathway can contribute to conflicting immunological interactions with cancer.